2012
DOI: 10.1103/physrevb.86.035105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of van der Waals interactions on the structural and elastic properties of black phosphorus

Abstract: The structural and elastic properties of orthorhombic black phosphorus have been investigated using first-principles calculations based on density functional theory. The structural parameters have been calculated using the local density approximation (LDA), the generalized gradient approximation (GGA), and with several dispersion corrections to include van der Waals interactions.It is found that the dispersion corrections improve the lattice parameters over LDA and GGA in comparison with experimental results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
271
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(311 citation statements)
references
References 70 publications
(113 reference statements)
31
271
1
3
Order By: Relevance
“…Fig. 9 shows the effect of CPI on the Poisson induced strains in SLBP (4,5) that is deformed in the x-direction. Fig.…”
Section: The Effect Of Cpi On Negative Poisson's Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 9 shows the effect of CPI on the Poisson induced strains in SLBP (4,5) that is deformed in the x-direction. Fig.…”
Section: The Effect Of Cpi On Negative Poisson's Ratiomentioning
confidence: 99%
“…Fig. 16 shows the relaxed structure for SLBP (4,5) with free boundary conditions applied in the y-direction. Fig.…”
Section: Cpi and Edge Stress-induced Bendingmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[14][15][16][17][18][19] The accidental degeneracy discussed above has not been reported in these previous DFT calculations. It is also worth mentioning that LDA usually overbinds the atomic structure yielding smaller bond lengths and lattice constants than experiment.…”
mentioning
confidence: 70%
“…Experimental and theoretical studies showed that few-layer black phosphorus displays high and anisotropic carrier mobility [14,15], excellent electron-channel contacts [1], and electronic and optical properties that are tuned by the stacking order [4,16,17], in-plane strain [2], and external electric field [2,7,[18][19][20]. Meanwhile, high performance field-effect transistors based on black phosphorus have been successfully fabricated with a carrier mobility up to 1000 cm 2 /V/s [1] and an ON/OFF ratio up to 10 4 at room temperature [12].…”
Section: Introductionmentioning
confidence: 99%